Strength of mesh augmented rotator cuff repair - Lim, Zhuang Chen (2017)
There are different ways of rotator cuff repair such as anchor repair, mesh augmentation repair and patch augmentation repair on current surgical methods. However, re-tear of rotator cuff happens frequently after surgery. Therefore, it is important to find the best repair technique through biomechanical performance. The objective of this study is to evaluate the strength of the rotator cuff repair using surgical mesh and suture. Eight sheep shoulder specimens with full thickness tear were repaired with Enveloped Premilene® Mesh bridge with horizontal mattress stitch repair, which include Premilene® mesh and Ethibond Excel 2-0 suture by mattress stitch, were sewn on fully torn infraspinatus tendon. All eight specimens were then mounted on a custom-designed fixture, which was secured onto the Instron 5566 machine. Specimens were cyclic loaded between 10 N to 180 N at 8.33 mm/s for 3000 cycles. Gap formation were recorded every 500 cycles until it reaches 3000 cycles, followed by load to failure test. The results showed that the means gap formation and the mean ultimate failure load was 4.17 ± 1.21 mm and 426.35 ± 17.84 N respectively. The mode of failure for all eight shoulder specimens were suture pull-out through tendons. Comparing to other methods, Dual-row Enveloped Premilene® Mesh bridge with horizontal mattress stitch repair is relatively weaker than existing methods with anchors but may be applicable to use together with existing anchors.